ANALISIS PRODUKTIVITAS DAN PERHITUNGAN WAKTU BAKU DI BAGIAN MACHINERY DENGAN MENGGUNAKAN METODE WORK SAMPLING DI UNIT MACHINERY AND TOOL PT.MEGA ANDALAN KALASAN - Agustian, Devi (Jurnal Nosel, 2014)
The purpose of this research is to quantify the productivity and standard time achieved by the operator in the manufacture of objects produced in turning machine C6232B1, CNC Turning machine Doosan Puma GT2100, cutting machine at machinery division PT. Mega Andalan Kalasan by using work sampling method. This research is descriptive quantitative. Research by the work sampling method executable instantaneously at the times specified by the researcher visits. Data collection is carried out by observation, interviews, and direct observation with the operators work activity during productive or idle time.Based on data and results of research analysis gained: (1) Percentage of productivity from  turning machine operator, CNC machine operator, and cutting machine operator are 83.40%, 82.26%, 83.80%. (2) Standard time achieved by turning machine operator are Spindle Luar5,12 minutes, Slider Luar1,16 minutes, Mur Handle Pendorong6,68 minutes, Tutup Boom21,41 minutes, Ring Rangka Depan0,97 minutes, Bush Pipa Pengungkit2,27 minutes, Baut Gulungan Kabel4,97 minutes, As Pengunci1,25 minutes, Dudukan Head And Foot End 2,47 minutes, Alur Tiang Panci 11,42 minutes, Engsel Penompang Betis 2,54 minutes, Handle Ungkit Gasspring Pendek2,04 minutes, As Dudukan Panel3,26 minutes, Sambungan Motor Backraise 3,36 minutes, Mur Castor  6,53 minutes. Standard time achieved by cutting machine operator are Engsel Penompang Betis10,54 minutes, Mur Castor Ms6,56 minutes, Dudukan Motor Backraise6,84 minutes, Rumah Ulir22,39 minutes, Mur Castor Stainless9,56 minutes, Mur Pengungkit Kanan4,43 minutes, Mur Pengungkit Kiri5,09 minutes, Tutup Penompang Betis12,92 minutes, Rumah Tiang Betis11,89 minutes, Sock Pendorong8,14 minutes, Roda15,27 minutes, Slider Luar1,10 minutes, Ulir Pendorong Backrest3,36 minutes, Mur Pengangkat Chasis3,05 minutes. Standard time achieved by CNC machine operator are Porok Castor 8,21 minutes, Baud Engsel Kaki 4,22 minutes, Pin Pengunci 3,91 minutes, Pin Pengungkit 2,43 minutes, Pin Backreise 2,57 minutes, Engsel 7,36 minutes, Pin Roda 2,98 minutes, Pin Motor 2,99 minutes.The average from percentage of standard time differences every operators from turning machine operator, cutting machine operator, and CNC machine operator are 11.73%, 11.5%, and 11.75%. The average is not exceed than company standard tolerance 25%.